Composition and distribution of the microphytoplankton from Guamá River between Belém and São Miguel do Guamá, Pará, Brazil - Monteiro, Milena Daisy Ribeiro; Melo, Nuno Filipe Alves Correia de; Silva Alves, Marcelo Augusto Moreno da; Paiva, Rosildo Santos (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2009)
The microalgae are responsible for a great part of the primary productivity of the aquatic ecosystems. Any environmental disturbance that affect the quality of water will result in an alteration of the structure of the phytoplankton community and, consequently, of all the trophic web. This work presents the composition and density of microphytoplankton of the Guamá river based on the analysis of 25 samples collected along the passage situated between Belém and São Miguel do Guamá. Were identified 85 taxa belonging to the Dinophyta (1%), Cyanophyta (4%), Chlorophyta (20%), and Bacillariophyta (75%). Aulacoseira granulata (Ehrenberg) Simonsen, Coscinodiscus oculus-iridis Ehrenberg, Oscillatoria sp., Polymyxus coronalis L.W. Bail, Surirella guatimalensis Ehrenberg, Thalassiorira eccentrica (Ehrenberg) Cleve, and Triceratium favus (Ehrenberg) Wallich were the most frequent species. The maximum density was 742.000 organisms/liter, verified in station 21, and the minimum density observed was 9.280 organisms/liter, found in station 10.
Keywords: Phytoplankton; Guamá River; Amazon estuary